'Sending them beyond the Sea': Andrew Marvell, the Earl of Clare, and Tutoring in the Restoration. Issue 1 (24th May 2017) - Coster, Steph
Abstract : Going 'beyond the sea' was an important part of education in the seventeenth century. We know that Marvell traveled extensively in Europe as a tutor in the 1640s, and with William Dutton in the 1650s. Marvell's career as a tutor has received a good deal of attention from modern scholars. Thanks to Nigel Smith's recent biography and Nicholas von Maltzahn's chronology of Marvell's life, we have a detailed account of the years Marvell was employed in this type of service. Yet existing commentary on Marvell and tutoring covers only a brief period in the 1640s and 1650s, up until the point Marvell entered the secretariat in 1657. This essay examines a newly discovered letter suggesting that Marvell continued to be involved in the tutoring of the nobility in the Restoration – as a client of Gilbert Holles, Earl of Clare, Marvell was searching for nonconformist tutors with extensive travel experience for Clare's son. The letter is significant for two reasons. Firstly, it underlines the value attached to European travel in the education of the nobility and gentry. Secondly, it provides valuable information about Marvell's circle of acquaintances in the Restoration. The newly found link between Clare and Marvell expands the network of puritan politicians with whom we know Marvell associated. Clare's puritan interests mattered to his choice of tutor. Looking closely at the kind of service Marvell offered Clare helps us better to understand Marvell's attitude to nonconformity, and how this manifests itself in his writing in the 1670s.